2008
DOI: 10.1111/j.1095-8649.2008.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and trophic position determine mercury concentration in the straight fin barb Barbus paludinosus, a small fish species in Lake Awassa, Ethiopia

Abstract: The diet, habitat use and mercury concentration of the small fish species, the straight fin barb Barbus paludinosus, were studied in Lake Awassa, Ethiopia, for a period of 1 year from February 2003 to January 2004. Stable isotope signatures of nitrogen and carbon in different total length (L T ) classes were used to determine trophic positions and organic carbon sources, respectively. Barbus paludinosus mainly occupied the protected benthic habitats (littoral and profundal) of the lake. The d 13 C values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Stunting in growth of individuals with long lifespan may cause higher mercury levels than in individuals under good growth conditions because of an increasing proportion of mercury per unit body mass (Campbell et al, 2006;Desta et al, 2007a). Growth in length of European minnow and brown trout stagnates at ages of around 5 and 8 years, and at lengths around 8 and 30 cm, respectively, but no marked change in mercury contamination seems to occur in either of the species.…”
Section: Discussionmentioning
confidence: 96%
“…Stunting in growth of individuals with long lifespan may cause higher mercury levels than in individuals under good growth conditions because of an increasing proportion of mercury per unit body mass (Campbell et al, 2006;Desta et al, 2007a). Growth in length of European minnow and brown trout stagnates at ages of around 5 and 8 years, and at lengths around 8 and 30 cm, respectively, but no marked change in mercury contamination seems to occur in either of the species.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies from tropical localities have shown that Hg concentration in fish generally increases with both size [ 3 , 54 , 61 ] and trophic position as the result of contaminant accumulation with the exposure time and biomagnification [ 24 , 62 ]. A study carried out in Lake Awassa (Ethiopia) reported the influence of habitat use in the variation of Hg concentration in the piscivorous species Barbus paludinosus [ 63 ] with fish inhabiting the pelagic zone having higher Hg concentration than those preying on benthic organisms. Habitat use is well known in temperate studies to reflect Hg concentration in organisms in lakes with pelagic dwellers having higher concentrations than littoral organisms due to habitat-specific bioaccumulation of MeHg in prey [ 38 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These activities as well as population growth have substantially increased the burden of contamination. Recent studies on fish fillets have revealed high levels of mercury (Hg) in Barbus fish species from the lake (Desta et al, 2006(Desta et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%